Subliminal meaning-contingent attentional orienting: The role of attentional control setting based on displaywide features - Wang, Huiyuan; Yang, Jiajia; Gao, Yulin; Zhang, Ming (Frontiers in Psychology, 2022)
People's subjective factors can affect the spatial allocation of attention, and objects that are more in line with people's expectations are easier to attract attention. In the current study, we wanted to know whether the meaning-contingent spatial attentional orienting could occur at the subliminal level, that is, whether conscious awareness was needed, and which attentional control settings worked. The current study employed a modified spatial cueing paradigm and the cues were made imperceptible by backward masking. The results showed that the capture effects of the left and the right positions stemmed from the meaning-contingent attentional control setting based on displaywide features, while the inhibition effect of the lower position and the capture effect of the upper position stemmed from the abrupt onset of subliminal cues and their masks. It is concluded that the attentional orienting of meaning contingency could occur at the subliminal level, which was not restricted by conscious perception. In particular, the attentional control setting based on displaywide features played an important role in spatial attentional orienting, which was manifested in the consistent capture effects on the horizontal sides. This study refined and separated the spatial attentional orienting effects, supported the contingent involuntary attentional orienting hypothesis, and expanded its scope of application.